Anna Karenina - 2 Based on a Novel by Leo Tolstoy - Tolstoj, Lev Nikolaevic
Cutting straight to the heart of Tolstoy's classic novel, this innovative Channel 4 adaptation draws on the realism and raw emotion that defines this unique masterpiece. Set in 19th century Russia, from the decadent social surroundings of the St Petersburg palaces to the simplest of rural life, Anna Karenina is the story of three contrasting couples whose dilemmas strike a contemporary chord in another century. [www.play.com]